Phylogenetics of Malaysian Betta bubblenest brooders based on 16S rRNA - Jamaluddin, Jamsari Amirul Firdaus; Sharifuddin, Noraznita; Mohd Nor, Siti Azizah; Lim, Teow Yeong (2009)
The phylogenetic relationships among thirteen individuals of all seven Malaysian bubblenester fighting fish, Betta were examined by using an approximately 700 bp of the mitochondrial 16S ribosomal RNA (16S rRNA) sequence. With strong bootstrap support for all taxa, the result showed monophyletic status of three bubblenest brooder groups: coccina, bellica and splenden. The coccina group was found to be the sister-group to the remaining bubblenester group. B. livida and B. coccina was likely to be the most recent divergent species of these groups.